"Justice demands that you find this man not guilty": A transitivity analysis of the closing arguments of a rape case that resulted in a wrongful conviction. (26th July 2018) - Bartley, Leanne Victoria
Abstract : Courtroom language is renowned for being strategic and a powerful means of manipulation, which may explain why criminal cases can sometimes result in a wrongful conviction. One such case is examined here, whereby an innocent man is convicted by a jury for the rape of a minor. Through a look at the closing arguments by the prosecution and defence attorneys, we can gain insights into why the defendant finds himself wrongly convicted of sexual assault. To show how the accused and others are portrayed, a combination of Critical Discourse Analysis and corpus linguistics is employed, with special attention paid to the transitivity patterns present in the dataset.